Analysis of Students' Responses to Vocabulary Learning Through Songs “Hero” by Mariah Carey for Senior High School in Cianjur - Damayanti, Hepy; Mauriyat, Arham (IKIP Siliwangi, 2025)
English, as an international language, plays a crucial role in various aspects of life, from education to the workplace. This study aimed to explore how eleventh-grade high school students respond to mastering English vocabulary through songs. The research employed a quantitative method, collecting data through questionnaires completed by 21 students. The results indicated that most students responded positively to using songs as a learning medium. It was found that songs not only increased their motivation but also enhanced their concentration and vocabulary skills. These findings support the integration of songs into language learning, making the process more interesting and effective. Additionally, regularly using new vocabulary in daily conversations helps students retain it and avoid forgetting previously learned words. This practice is crucial for ensuring long-term vocabulary retention and overall language proficiency. Integrating songs and encouraging daily use of new words can significantly enhance students' language learning experiences.